Children’s voice and participation in all school contexts - Parreiral, Sílvia (2013)
This paper presents a case study research based on content analysis of student group interviews that explores democratic experiences and student involvement in school. Fifteen 5th, 7th and 9th label classes were interviewed about their perceptions as students and partners in the decision-making process on matters that concern them, as children/teenagers with rights and justice ambitions. Class-directors were also interviewed to understand their views on how students feel about being (not being) heard in moments and places of decision, which would make them not just passive future adults. Results indicate that students are disappointed with the fact that decisions are made and implemented by the executive council without their participation. Teachers’ perceptions show that it is important for children to be heard more and participate in different school contexts but, in fact, school doesn´t yet recognize the relevance and importance of a more active and real participation of students in several contexts, mainly at these ages. It is then argued that citizenship education should promote further research and critical reflection in order to identify a new model of practical sense where students are seen as fundamental elements of a well succeeded educational dynamics in school.